Effect of volume on eccentric overload iInduced postactivation potentiation of jumps - de Keijzer, K. L.; McErlain-Naylor, S. A.; Dello Lacono, A.; Beato, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the postactivation potentiation (PAP) effects of different eccentric overload (EOL) exercise volumes on countermovement-jump (CMJ) and standing-long-jump (LJ) performance. Methods: In total, 13 male university soccer players participated in a crossover design study following a familiarization period. Control (no PAP) CMJ and LJ performances were recorded, and 3 experimental protocols were performed in a randomized order: 1, 2, or 3 sets of 6 repetitions of flywheel EOL half-squats (inertia=0.029 kg·m2). Performance of CMJ and LJ was measured 3 and 6 minutes after all experimental conditions. The time course and magnitude of the PAP were compared between conditions. Results: Meaningful positive PAP effects were reported for CMJ after 2 (Bayes factor [BF10]=3.15, moderate) and 3 (BF10=3.25, moderate) sets but not after 1 set (BF10=2.10, anecdotal). Meaningful positive PAP effects were reported for LJ after 2 (BF10=3.05, moderate) and 3 (BF10=3.44, moderate) sets but not after 1 set (BF10=0.53, anecdotal). The 2- and 3-set protocols resulted in meaningful positive PAP effects on both CMJ and LJ after 6 minutes but not after 3 minutes. Conclusion: This study reported beneficial effects of multiset EOL exercise over a single set. A minimum of 2 sets of flywheel EOL half-squats are required to induce PAP effects on CMJ and LJ performance of male university soccer players. Rest intervals of around 6 minutes (>3 min) are required to maximize the PAP effects via multiple sets of EOL exercise. However, further research is needed to clarify the optimal EOL protocol configurations for PAP response.